What Bigots Do Say: A Reply to DiFranco. (30th September 2016) - Caso, Ramiro; Lo Guercio, Nicolás
Abstract : Neutral Counterpart Theories of slurs hold that the truth‐conditional contribution of a slur is the same as the truth‐conditional contribution of its neutral counterpart. In (2015), DiFranco argues that these theories, even if plausible for single‐word slurs like 'kike' and 'nigger', are not suitable for complex slurs such as 'slanty‐eyed' and 'curry muncher', figurative slurs like 'Jewish American Princess', or iconic slurring expressions like 'ching chong'. In this paper, we argue that these expressions do not amount to genuine counterexamples to neutral counterpart theories of slurs. We provide a positive characterization of DiFranco's examples that doesn't deviate from the core of those theories.